2020
DOI: 10.2478/pjmpe-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of imaging properties of novel contrast agents based on gold, silver and bismuth nanoparticles in spectral computed tomography using Monte Carlo simulation

Abstract: In the present paper, some imaging properties of nanoparticles-based contrast agents including gold, bismuth, and silver were assessed and compared with conventional (iodinated) contrast agent in spectral computed tomography (CT). A spectral CT scanner with photon-counting detectors (PCD) and 6 energy bins was simulated using the Monte Carlo (MC) simulation method. The nanoparticles were designed with a diameter of 50 nm at concentrations of 2, 4, and 8 mg/ml. Water-filled cylindrical phantom was modeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The MC model was previously validated and utilized by a previous investigation. 16 A point source at a distance of 540 mm from the isocenter was defined. An angular bias for photon emissions was considered to reduce the run-time and avoid photon emission in other directions.…”
Section: Methodsmentioning
confidence: 99%
“…The MC model was previously validated and utilized by a previous investigation. 16 A point source at a distance of 540 mm from the isocenter was defined. An angular bias for photon emissions was considered to reduce the run-time and avoid photon emission in other directions.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation indicated that high- Z NPs had a higher CNR than iodine. 77 Jo et al used the Monte Carlo method to simulate SPCCT imaging and DECT for three-material decomposition (lipid, iodine, and gold nanoparticles) to identify vulnerable plaques in the coronary artery. The proposed technique analyzes the composition of plaques by quantifying the number of lipids and calcification.…”
Section: Gold (79) Nanoparticlesmentioning
confidence: 99%
“…77 While another study suggested that iron oxide NPs coated with Bi (Fe 3 O 4 @Bi) or Au (Fe 3 O 4 @Au) produced the same image quality but better quality images were obtained between 100–120 keV for Bi-coated NPs. 88 Furthermore, bismuth sulfide (Bi 2 S 3 , 276 nm size) flower-like nanostructures or nanoparticles synthesized by a green strategy (highly monodispersed) showed high biocompatibility and absorption in the NIR range and excellent spectral CT imaging capability. The administered formulation generated accurate spectral CT images for the gastrointestinal tract as well as assisted with the diagnosis of intestinal obstruction as a result of growing tumor in vivo , as shown in Fig.…”
Section: Bismuth (83) Nanoparticlesmentioning
confidence: 99%
“…Here, the EF is defined as the ratio of the DNA damages in the presence and lack of NPs, and DEF refers to the ratio of the delivered dose in the presence and absence of NPs. There has been considerable work on the radiosensitizing efficacy of NPs, including mathematical, 24 , 25 in silico, 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 and in various biological systems including molecular solutions, 5 , 36 , 37 , 38 cell‐based models 39 , 40 , 41 , 42 , 43 , 44 and in vivo. 45 , 46 Ionizing radiation causes a variety of direct and indirect damage to DNA, including isolated (single‐strand break (SSB) and single base damages) and clustered/complex lesions (multiple DSBs and/or closely spaced (within 10–20 base pairs) non‐DSB (double strand break) lesions, such as oxidized bases and abasic sites) that affect genome integrity and DNA biochemistry.…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...mentioning
confidence: 99%